The debs - McBride, Susan , 1964- (Delacorte Press, 2008)
Rising high school seniors and life-long best friends Laura, Mac, and Ginger hope for invitations to be introduced to Houston, Texas, society as Glass Slipper Debutantes, while each faces family and boyfriend issues and Jo Lynn plots Laura's downfall